Variation of luminescence sensitivity of quartz grains from loess in eastern Tibetan Plateau and its provenance significance - Liu, Li; Yang, Shengli; Liu, Xiaojing; Li, Pushuang; Wang, Haiyan; Zhou, Jiantao (Frontiers in Earth Science, 2022)
The loess deposits are widely distributed in the eastern Tibetan Plateau (ETP) are important archives for reconstructing the paleoenvironment changes and dust history of the Tibetan Plateau. Insufficient investigations on the source of the ETP loess have limited our understanding of dust transportation and paleoenvironmental implications. The quartz luminescence sensitivity holds great potential in the tracing of eolian dust sources. Detailed quartz luminescence sensitivity investigations will provide new insights into the dust source and transportation in the ETP. In this paper, we selected quartz grains in loess from different sites of the ETP to investigate the variation of luminescence sensitivity by testing the 110°C TL peak and OSL sensitivities of quartz grains. Our results show that: 1) The quartz luminescence sensitivity of loess at different locations was significantly different in the ETP. The luminescence sensitivity values of MC, XJ, and WCH were much higher than those of XS and ZQ; 2) The sensitivity values of the 110°C TL peaks and OSL sensitivity in paleosols and loess show distinct differences; 3) The quartz luminescence sensitivity of the ETP loess is mainly influenced by the dust source. Our results reveal that the luminescence sensitivities of quartz grains show great potential for identifying the loess source in the ETP.